5PSQ-076 Patients' satisfaction after changing from 150mg to 300mg secukinumab pen presentation. Issue 1 (23rd March 2023) - Castro Salinas, P; Charques, V; Retamero, A; Mendiola, S; Figueras, A; Serrais, J; Martínez, J; Ferrandez, D
Abstract : Background and Importance: Secukinumab is an anti-interleukin-17 drug used for psoriasis, psoriatic arthritis or spondyloarthritis. Recently, our hospital changed from 150mg to 300mg secukinumab pen presentation in order to simplify treatment and facilitate administration. However, as patients often have other expectations, desires and priorities evaluating the degree of satisfaction allows us to identify deficiencies and causes of dissatisfaction. Aim and Objectives: To determine patients' satisfaction after changing from 150mg to 300mg secukinumab pen presentation. Material and Methods: Retrospective study carried out in a regional hospital. Patients on treatment with secukinumab 2x150mg/month who changed presentation to 300mg/month during November-December 2021 were included. Patients who hadn´t taken both presentations for at least 4 months and patients impossible to locate were excluded. Those who gave their verbal consent underwent a telephone survey. Variables collected: sex, age, drug indication, treatment duration, self-administration, pain measured with VAS(Visual Analogue Scale) with both presentations, presence of administration site reactions with both presentations, satisfaction with pen change measured from 0 to 10 (0 minimum-10 maximum), 300mg pen discontinuation and reason. Qualitative variables were expressed as frequency and percentage and quantitative ones as mean and standard deviation. Statistical analysis was performed with Excel (v.12.0). Results: Total number of patients with 300mg pen presentation:33. Included: 24 (72.2%). Women:9(42.9%). Age:49(13.9). Patients with psoriasis:19(79.2%), psoriatic arthritis 4(16.7%) and spondyloarthritis 1(4.2%). Treatment duration (months) 38.7(22.6). Patients who self-administered medication: 23(95.8%). VAS with 150mg presentation 1.8(1.2) and with 300mg presentation 2.2(1.9). Regarding the 150mg presentation, 2(8.3%) patients reported having bruises at the injection site and regarding the 300mg presentation, 3(12.5%) reported having suffered swelling that reverted spontaneously. Two(8.3%) had to discontinue the 300mg presentation due to severe pain during administration. Regarding change satisfaction, 1(4.1%) referred to the change as indifferent, 2(8.3%) as not satisfactory and 21(87.5%) as satisfactory, with the average satisfaction being 8.0(2.2). Conclusion and Relevance: Changing from 150mg to 300mg secukinumab pen presentation was considered satisfactory for 87.5% of patients. Two patients suffered greater pain during administration, leading to a return to the previous presentation. It would be advisable to carry out additional follow-up in order to detect possible reactions at the administration site or greater pain after the change of presentation. References and/or Acknowledgements: Conflict of Interest: No conflict of interest